Toleransi Beragama dalam Sejarah Kekaisaran Islam: Pelajaran dari Andalusia dan Kesultanan Utsmani - Muhammad Jailani Jailani (UPT Publikasi Ilmiah, 2025)
This study examines the issue of religious tolerance in Islamic civilization, focusing on two major empires: Andalusia (711–1492) and the Ottoman Empire (1299–1922). The topic is significant as it challenges the stereotype of Islam as an exclusive faith by highlighting historical periods when pluralism and coexistence served as the foundation of a prosperous civilization. The research aims to identify the theological and social principles that supported tolerance in these two contexts and to assess their relevance to the modern world, which continues to face growing polarization and identity-based conflicts. This study relies entirely on library research, examining legal documents, theological writings, and intellectual works to explain the concept, foundations, and implications of religious tolerance in these two empires. This approach enables a deeper historical-comparative understanding grounded in textual and scholarly sources. The findings reveal that Andalusia promoted cultural and intellectual coexistence, while the Ottoman Empire institutionalized tolerance through the millet system, ensuring legal and social autonomy for non-Muslim communities. Both models were grounded in the Islamic principles of justice (‘adl) and public welfare (maṣlaḥah) as the foundation for enduring social harmony. The study concludes that Islamic tolerance is not merely a political accommodation but deeply rooted in Islamic ethical theology, emphasizing justice, diversity, and compassion. These historical models provide valuable insights for shaping modern social and educational policies that foster pluralism, equity, and sustainable peace in today’s globalized world.